Credibility of central banks inflation forecasts - Karolina Tura-Gawron (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
Modern monetary policy focuses on credibility and shaping consumers' inflation expectations. According to the concept of inflation forecast targeting (IFT), inflation forecasts play a crucial role in the instrument rate decision-making process and may be a specific intermediate target. The aim of the study is to analyse the credibility of inflation forecasts published by the central banks of England, Sweden and Norway. The article presents the proposition of an inflation forecast credibility index. The inflation forecasts' credibility index may be calculated for all types of inflation forecasts made by central banks, which implement an inflation targeting (IT) regime. It consists of three main elements: the accuracy of the forecasts, the similarity of the forecasts and the inflation forecast deviations from the inflation target. The credibility index has been calculated for the inflation forecasts made by central banks of England, Sweden and Norway. The research conducted shows that most of the inflation forecasts published in selected central banks were credible.
Keywords: E58; E52; E47; 330; inflation forecasts targeting; inflation forecast; inflation forecast credibility index; inflation expectations